2020
DOI: 10.1007/s12306-020-00650-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the young adult hip joint using plain radiographs

Abstract: Radiographic examination remains the mainstay of the initial assessment of the young adult hip; however, common parameters are required to assist in the formation of accurate diagnoses and appropriate management plans. This paper aims to summarise the most important aspects of the assessment of plain radiographs performed on the young adult hip joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
0
15
0
1
Order By: Relevance
“…Although the limitations of 2D measurements in assessing complex three-dimensional (3D) anatomies are well known, they still represent the gold standard in the preoperative planning of hip surgeries due to the lack of adequate 3D measurement methods. Studies have shown that 2D measurements are biased by the projection of the anatomy in the radiographs [16][17][18][19][20][21][22][23] and the intra-and inter-reader variability of the measurement methods [20,[24][25][26]. This underlines the need for a more robust 3D preoperative planning method in order to accurately determine and implement the optimal correction.…”
Section: Introductionmentioning
confidence: 99%
“…Although the limitations of 2D measurements in assessing complex three-dimensional (3D) anatomies are well known, they still represent the gold standard in the preoperative planning of hip surgeries due to the lack of adequate 3D measurement methods. Studies have shown that 2D measurements are biased by the projection of the anatomy in the radiographs [16][17][18][19][20][21][22][23] and the intra-and inter-reader variability of the measurement methods [20,[24][25][26]. This underlines the need for a more robust 3D preoperative planning method in order to accurately determine and implement the optimal correction.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed by another study who found that values of acetabular depth were close to each other in sacra of both sides. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The femoral head coverage (FHC) was measured using three vertical lines passing through the medial part of the hip joint space (line I), lateral edge of the acetabulum (line II) and lateral outline of femoral head (line III). The FHC was determined by the formula 13 : (Distance between lines I and II) ÷ (Distance between lines I and III) × 100 ( Fig.2a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deformidade da coxa vara, tem como uma das consequências a redução do comprimento em repouso dos músculos abdutores da coxa, por conseguinte, se traduz clinicamente com redução da força desse grupamento muscular, e que pode causar a marcha de Trendelenburg, caracterizada por uma tendência de queda para o lado oposto durante a fase de apoio, marcha típica de pacientes com disfunção dos músculos abdutores, principalmente do glúteo médio, no qual tem a maior função abdutora (Popat et al, 2020).…”
Section: Autor Títulounclassified